Broader impacts of an intervention to transform school environments on student behaviour and school functioning: post hoc analyses from the INCLUSIVE cluster randomised controlled trial. Issue 5 (15th May 2020) - Bonell, Christopher; Dodd, Matthew; Allen, Elizabeth; Bevilacqua, Leonardo; McGowan, Jennifer; Opondo, Charles; Sturgess, Joanna; Elbourne, Diana; Warren, Emily; Viner, Russell M
Abstract : Background: We have previously reported benefits for reduced bullying, smoking, alcohol and other drug use and mental health from a trial of 'Learning Together', an intervention that aimed to modify school environments and implement restorative practice and a social and emotional skill curriculum. Objectives: To conduct post hoc theory-driven analyses of broader impacts. Design: Cluster randomised trial. Settings: 40 state secondary schools in southern England. Participants: Students aged 11/12 years at baseline. Outcomes: Student self-reported measures at 24 and 36 months of: cyberbullying victimisation and perpetration; observations of other students perpetrating aggressive behaviours at school; own perpetration of aggressive behaviours in and outside school; perceived lack of safety at school; participation in school disciplinary procedures; truancy and e-cigarette use. Results: We found evidence of multiple impacts on other health (reduced e-cigarette use, cyberbullying perpetration, perpetration of aggressive behaviours) and educational (reduced participation in school disciplinary procedures and truancy) outcomes. Conclusion: These analyses suggested that the intervention was effective in bringing about a broader range of beneficial outcomes, adding to the evidence that the intervention is a promising approach to promote adolescent health via an intervention that is attractive to schools. Trial registration number: ISRCTN10751359 .